WHEN DIPLOMATS BECOME UNWELCOME: THE INDIA-PAKISTAN 2025 PERSONA NON GRATA - Adzkia, Nurul; Pratama, M. Riezky Putra; Adepio, M. Ilham (UNTAG Law Review, 2025)
The 2025 diplomatic tension between India and Pakistan, culminating in the mutual expulsion of diplomats under persona non grata status following a terrorist attack in Kashmir, highlights the use of diplomatic law as a political tool in strained bilateral relations. This study aims to analyze the regulations concerning persona non grata under the 1961 Vienna Convention on Diplomatic Relations (VCDR) and their application in the India-Pakistan case. Employing a normative legal research method with a statutory approach, data from primary, secondary, and tertiary legal sources is descriptively analyzed. The findings reveal that Article 9 of the VCDR grants the receiving state full discretionary authority to expel a diplomat without justification, a right exercised in this instance for political retaliation. Both nations justified their actions by alleging violations of Article 41 of the VCDR, which obligates diplomats to respect the laws of the receiving state. This case demonstrates that diplomatic immunity is not absolute and is subject to national security interests. The implication is that a legally sanctioned persona non grata action can be instrumentalized for political retribution, thereby undermining the very channels essential for communication and peaceful conflict resolution.